2009
DOI: 10.1017/s1368980009991704
|View full text |Cite
|
Sign up to set email alerts
|

Association between breast-feeding and anthropometry and CVD risk factor status in adolescence and young adulthood: the Young Hearts Project, Northern Ireland

Abstract: Objective: To examine the association between breast-feeding and blood pressure, anthropometry and plasma lipid profile in both adolescence and young adulthood. Design: Longitudinal study of biological and behavioural risk factors for CVD. Setting: The Young Hearts Project, Northern Ireland. Subjects: Schoolchildren aged 12 years and 15 years who participated in a crosssectional study of lifestyle and health, and who were followed up as young adults aged 20-25 years. Results: There was no significant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 32 publications
2
16
1
1
Order By: Relevance
“…They found a dependent effect between the length of breastfeeding and the incidence of overweight and obesity in children and adolescents. 24,25 In this study, among the boys, the length of breastfeeding showed a significant and inverse relation with the DBP. Among the girls, the length of exclusive breastfeeding showed a statistically significant and inverse relation with the BMI and SBP.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…They found a dependent effect between the length of breastfeeding and the incidence of overweight and obesity in children and adolescents. 24,25 In this study, among the boys, the length of breastfeeding showed a significant and inverse relation with the DBP. Among the girls, the length of exclusive breastfeeding showed a statistically significant and inverse relation with the BMI and SBP.…”
Section: Discussionsupporting
confidence: 49%
“…The unique composition of the nutrients in breast milk is qualitative and quantitatively different from any infant formula, as it contains bioactive substances, which affect the differentiation and proliferation of the fat cells, which can influence the tissue growth and development. 25 In line with these findings, the literature 26 affirms that the increased obesity in infants results from early and incorrect weaning; deriving from dietary errors in the first year of life, mainly in the urban population, which give up breastfeeding early and replace it by a diet with too many carbohydrates, in higher than necessary amounts for the child's growth and development. One element that is frequently present in the ineffective breastfeeding context and is also related to excessive weight gain in infants is the use of artificial formulae.…”
Section: Discussionmentioning
confidence: 88%
“…Although studies examining the association between human milk feeding and CVD risks are not few, previous studies reached to contradictory results [13,21,22]. Several evidences suggest inverse association between BF, serum low-density lipoprotein cholesterol (LDL-C) and triglyceride levels (TG) [22][23][24], whereas others did not confirm such relationship [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Boyla anne sütü aras›nda doz ba¤›ml› iliflki bulunmad›¤› için anne sütü al›m süresinin etkisinin olmad›¤› da vurgulanm›flt›r (8). Baflka bir çal›flmada da, anne sütü alan çocuklar›n eriflkin boylar›n›n, anne sütü almam›fl olanlara nazaran anlaml› ölçüde uzun oldu¤u bildirilmifltir (ortalama olarak 1,7 cm boyda uzunluk) (9).…”
Section: Anne Sütünün Büyüme üZerine Etkileriunclassified